Mild Clinical Presentation of Acute Fatty Liver in the Second Trimester of Pregnancy - Alaeddine Yassin; Walid Denguezli; Anissa Fessi; Leila Njim; Raja Falah; Abdelfattah Zakhama; Mohamed Sakouhi (Case Reports in Obstetrics and Gynecology)
We report a case of 29 years old woman who was diagnosed with acute fatty liver of pregnancy at 23 weeks of gestation with unusual evolution (pregnancy prolonged until 36 weeks of gestation) to draw attention on the possibility of occurrence of this pathology in the second trimester of pregnancy even with a milder clinical presentation and course.